Co-creation a way of supporting development of neighbourhoodlevel transport innovations - Haufe, Nadine; Großmann, Astrid (AESOP, 2019)
Co-creation is a much discussed concept in the fields of urban planning, architecture, urban design and many more. In the HORIZON 2020 project SUNRISE, co-creation is the key concept to develop, implement, assess and facilitate learning about new ways to address common mobility challenges at the neighbourhood level. Towards this aim, six SUNRISE cities (Bremen, Budapest, Jerusalem, Malmö, Southend on Sea, Thessaloniki) foster co-creation processes with the explicit mandate to implement innovative solutions for and with their residents, and other stakeholders. The SUNRISE action neighbourhoods combine a blend of proven online and face-to-face co-creation methods, tools and techniques to bring together citizens, policy-makers and other stakeholders to learn from each other and to address urban challenges in neighbourhoods in transitions. This contribution gives an overview of various methods for coidentification and co-development of sustainable mobility solutions at the neighbourhood level, and discusses the advantages and disadvantages of online and offline tools. Keywords: co-creation; participation; mobility solutions; online and offline participation methods
Planning for Transition – book of proceedings 31; 2